1981
DOI: 10.1210/jcem-53-6-1310
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin,somatostatin and Neurotensin-Like Immunoreactivity in Bronchial Carcinoma

Abstract: Bombesin, a regulatory peptide found in adult lung and in higher concentration during development in the foetal lung, has potent biological actions which include the ability to stimulate the release of a number of hormones. Radioimmunoassay of extracts of tumour, lung and plasma from patients with bronchial carcinoma revealed very high tissue bombesin concentrations in two oat cell carcinomas, with lower levels in two out of six adenocarcinomas exceeding the concentrations found in normal lung. The oat cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…Peptides related to bombesin, including gastrin-releasing peptide (GRP) and the neuromedins, are widely distributed in normal mammalian tissues (10)(11)(12)(13)(14)(15)(16) and also are found in high levels in human pulmonary (17)(18)(19)(20) and thyroid (21) tumors. The finding that bombesin is mitogenic (9) and the wide distribution of endogenous mammalian analogues of bombesin strongly suggest that this family of peptides may play a role in the control of both normal and abnormal animal cell growth.…”
mentioning
confidence: 99%
“…Peptides related to bombesin, including gastrin-releasing peptide (GRP) and the neuromedins, are widely distributed in normal mammalian tissues (10)(11)(12)(13)(14)(15)(16) and also are found in high levels in human pulmonary (17)(18)(19)(20) and thyroid (21) tumors. The finding that bombesin is mitogenic (9) and the wide distribution of endogenous mammalian analogues of bombesin strongly suggest that this family of peptides may play a role in the control of both normal and abnormal animal cell growth.…”
mentioning
confidence: 99%
“…It is conceivable that the immunoreactive material is released into the general circulation where it may be implicated in the pathogenesis of paraneoplastic syndromes. Previously, NTLI has been shown to be present in endocrine pancreatic tumours (Blackburn et al, 1980;Feurle et al, 1981;Gutniak et al, 1980;Theodorsson-Norheim et al, 1983) and it also was found in human small cell lung carcinomas (Wood et al, 1981(Wood et al, , 1983. At present, the only cell lines known to produce NTLI have been derived from a rat medullary carcinoma of the thyroid and a rat phaeochromocytoma (Tischler et al, 1982;Zeytinoglu et al, 1980).…”
Section: Resultsmentioning
confidence: 95%
“…SCLC is known to secrete bombesin-like peptides (20)(21)(22) that might act as autocrine growth factors (2,25). Thus it was plausible but not proven that an antagonist to bombesin/GRP would inhibit SCLC growth, so we tested the effects of peptides A and D on SCLC cells in vitro.…”
Section: Peptide a And Peptide D Inhibit The Growth Of Sclc Cellmentioning
confidence: 99%
“…SCLC constitutes 25% of lung cancers and is, therefore, of major clinical and economic importance. Evidence that bombesin-like peptides, which are secreted by these tumors (20)(21)(22), can act as autocrine growth factors (25) has prompted the search for clinically useful GRP antagonists. We have presented evidence that two peptides that are antagonists of GRP and vasopressin profoundly inhibit the growth of SCLC cells in vitro although the participation of other growthpromoting peptides cannot be excluded.…”
Section: Peptide a And Peptide D Inhibit The Growth Of Sclc Cellmentioning
confidence: 99%
See 1 more Smart Citation